Assessment of Knowledge and Practice of Menstrual Hygiene Management among Adolescent School Girls in Ahmedabad City - Balat, Martina S; Sahu, Saurabh Kumar; Patel, Mitesh (National Journal of Community Medicine, 2019)
Background: Menstrual hygiene is inadequately acknowledged and has not received proper attention. Unhygienic menstrual prac- tices can affect the health of the girls and there is an increased vul- nerability to reproductive tract infections. The study was con- ducted to assess the knowledge and practice of menstrual hygiene among adolescent school girls in Ahmedabad city. Methods: A cross-sectional study was conducted among 430 ado- lescent girls from four schools in the Ahmedabad city. Data were collected during September to November 2016 using a pre-tested structured questionnaire in the local language (Gujarati). Results: Mean age at menarche was 13.4±1.04 and range between 11-16yrs. In this study, 46.9% and 48.1% of girls had good knowl- edge and practice of menstrual hygiene respectively. For 54.8% girls, the main sources of information about menstrual hygiene were Mother. Only 8.1% of girls knew about the source of blood during menses. 56.2% of girls used a sanitary pad. Only 7.0% changed pads or clothes more than three times a day. Conclusions: Based on this study were to conclude that less than half of girls had good knowledge and practices regarding men- struation. This situation can be tackled by giving health education to girls and creating awareness among parents.